PENGEMBANGAN PENGGUNAAN MICROSOFT WORD DAN EXCEL UNTUK EFISIENSI BELAJAR SISWA DI MTS ISLAMIYAH WONGSOREJO - Zaehol Fatah; Nasywa Faiz Atillah Mifta (Jurnal Padamu Negeri, 2026)
This study aims to develop the use of Microsoft Word and Microsoft Excel as supporting tools to enhance learning efficiency among students at MTS Islamiyah Wongsorejo. The program was conducted through seminars and hands-on practice focusing on mastering both basic and advanced features of the applications. The research employed a developmental approach consisting of preparation, implementation, and evaluation stages. The findings indicate a significant improvement in students’ digital skills, particularly in preparing academic documents using Word and managing data charts through Excel. Furthemore, the activities encouraged active participation, increased learning motivation, and aligned with the demands of the independent curriculum, which emphasizes digital literacy and creativity. Therefore, the integration of Word and Excel proved effective in supporting students’ learning efficiency while preparing them to face academic challenges and professional demands in the digital era.